Incremental diagnostic accuracy of computed tomography myocardial perfusion imaging over coronary angiography stratified by pre-test probability of coronary artery disease and severity of coronary artery calcification: The CORE320 study. (15th December 2015) - Sharma, Ravi K.; Arbab-Zadeh, Armin; Kishi, Satoru; Chen, Marcus Y.; Magalhães, Tiago A.; George, Richard T.; Dewey, Marc; Rybicki, Frank J.; Kofoed, Klaus F.; de Roos, Albert; Tan, Swee Yaw; Matheson, Matthew; et al.
Abstract: Background: Myocardial CT perfusion (CTP) has been validated as an incremental diagnostic predictor over coronary computed tomography angiography (CTA) in assessing hemodynamically significant stenosis. Objectives: To assess the diagnostic performance of CTA and CTP alone versus combined CTA–CTP stratified by Morise's pre-test probability and coronary artery calcium (CAC, Agatston) score. Methods: 381 individuals (153 low/intermediate-risk for CAD, 83 high-risk, 145 known CAD) were further stratified based on CAC score cut-offs of 1–399 and ≥ 400. Area under the curve for receiver operating characteristics (AUC) was calculated to assess the diagnostic performance. Reference standards were QCA ≥ 50% stenosis + corresponding SPECT summed stress score ≥ 1. Results: In both pre-test risk groups with an Agatston score of 1–399, AUCs of CTA–CTP were not significantly different than that from CTA alone. In the low/intermediate-risk group with CAC score 1–399, AUC for CTA–CTP (89) was higher than that for CTP (76, p = 0.003) alone. In the same group with CAC score ≥ 400, AUCs were higher for CTA–CTP (97) than that for CTA (88, p = 0.030) and CTP (83, p = 0.033). In high risk/known CAD patients with CAC 1–399, diagnostic performance for CTA–CTP (77) was superior to CTP (71, p = 0.037) alone. In the high risk/known CAD group with CAC score ≥ 400, AUCs for combined imaging were higher (86) than that for CTA (75, p < 0.001) as well as CTP (78, p = 0.020). Conclusions: The incremental diagnostic accuracy of CTP over CTA persists in patients across severity spectra of pre-test probability of CAD and coronary artery calcification. In patients with severe coronary calcification (CAC score ≥ 400), combined CTA–CTP has better diagnostic accuracy than CTA and CTP alone.